1964
DOI: 10.21236/ad0604033
|View full text |Cite
|
Sign up to set email alerts
|

Imperfections, a Main Contributor to Scatter in Experimental Values of Buckling Load

Abstract: AIJG 2 4 I DDCIRA E DISCLAIMER NOTICE When Government drawings, specifications, or other data are used for any purpose other than in connection with a definitely related Government procurement operation, the United States Government thereby incurs no responsibility nor any obligation whatsoever; and the fact that the Government may have formulated, furnished, or in anyway supplied the said drawings, specifications, or other data is not to be regarded by implication or otherwise as in any manner licensing the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Since these solutions are valid for all nand p, the linear combination of these solutions for nand p will be the general solution for the bifurcation modes in the limit of zero thickness of the shell. And these are the exactly the waveform type bifurcation modes, which coincides with the classical experimental results (Horton, 1965), e.g., periodic diamond type or Yoshimura's periodic triangle type bifurcation mode. Now, to obtain o the characteristic equation for A, we should note that t l = -w 2 is the one of roots of the quadratic…”
Section: Bifurcation Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…Since these solutions are valid for all nand p, the linear combination of these solutions for nand p will be the general solution for the bifurcation modes in the limit of zero thickness of the shell. And these are the exactly the waveform type bifurcation modes, which coincides with the classical experimental results (Horton, 1965), e.g., periodic diamond type or Yoshimura's periodic triangle type bifurcation mode. Now, to obtain o the characteristic equation for A, we should note that t l = -w 2 is the one of roots of the quadratic…”
Section: Bifurcation Analysissupporting
confidence: 87%
“…Since the earlier work by Lorenz(1908), many engineers have tried to obtain their theoretical results on the axially compressed cylindrical shell buckling (Donnell, 1934;Von Karman et al, 1941;Donnell et al, 1950;Yoshimura, 1955;Hoff et al, 1965;Lee, 1966;Hoff, 1966;Tennyson, 1969), but their results were not so much satisfactory comparing with some experimental works (Evensen, 1964;Almroth et al, 1964;Horton et al, 1965). The discrepancy between the theoretical results and the experimental results was considered to be due to imperfections (unavoidable deviations from the exact shape) (Von Karman, 1941;Donnell et al, 1950) and edge conditions (Nachbar et al, 1962;Almroth, 1966).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that both the shape and amplitudes of initial geometrical imperfections will have the influence on the load-carrying behavior of spherical shells. From testing cylindrical shells, Horton and Durham [18] concluded that the imperfection is a main contributor to scatter in experimental values of buckling load and buckling takes place first at the weakest section of the shell and the amount of buckling is a function of the area of weakness.…”
Section: Imperfect Spherical Shellmentioning
confidence: 99%
“…The mean value, E(A.p), which reflects the central tendency of A,p, shows that the buckling load decreases with the increase of the r/t ratio. The 95% confidence intervals of E(X,p), which are computed using the student t-distribution [55], are narrow compared to the range of Xpfrom unity to the lower bound (see Table 5 perfections were the main contributor to scatter in experimental values of A,pas well [13].…”
Section: Statistical Evaluation Of Resultsmentioning
confidence: 99%